Field evaluation of the Bioline Malaria Ag P.f/Pan rapid diagnostic test: causes of microscopy discordance and performance in Uganda - Kisakye Diana Kabbale; Bienvenu Nsengimaana; Francis D. Semakuba; Brian A. Kagurusi; Caroline Mwubaha; Innocent Wiringilimaana; Thomas Katairo; Shahiid Kiyaga; Monica Mbabazi; Samuel Gonahasa; Moses R. Kamya; Stephen Tukwasibwe; et al. (Malaria Journal)
Abstract Background Histidine Rich Protein 2 (HRP2)/pan-Lactate Dehydrogenase (pLDH) combination rapid diagnostic tests (RDTs) may address the shortcomings of RDTs that detect HRP2 alone. However, the relative contribution of the possible causes of discordant results (RDT-negative and microscopy-positive) and performance in field settings across Uganda are poorly quantified. Methods This study utilized samples from two cross-sectional surveys conducted in 32 districts at 64 sites across Uganda between November 2021 and March 2023 that enrolled 6354 febrile participants  ≥ two years of age. Discordant samples (negative by HRP2/pLDH RDT and positive by microscopy) underwent quantitative PCR (qPCR) to detect and quantify parasitaemia. Those confirmed to be positive for Plasmodium falciparum at > 1 parasites/microlitre (p/µL) were tested for pfhrp2 and pfhrp3 deletions using digital PCR. Those that were negative or had P. falciparum detected at ≤ 1 p/µL underwent Plasmodium species testing using nested PCR. The performance of the Bioline Malaria Ag P.f/Pan combination RDT was evaluated by comparison with microscopy and qPCR. Results There were 166 (8.4%) discordant samples out of 1988 microscopy positive samples. Of these, 90/166 (54.2%) were confirmed to contain P. falciparum at levels > 1 p/µL, whereas 76/166 (45.8%) were negative or had P. falciparum levels ≤ 1 p/µL. Only one P. falciparum positive sample was confirmed to have a deletion in pfhrp3. The primary reasons for RDT-negative, microscopy-positive discordance in samples testing negative for P. falciparum by PCR were non-falciparum species (37/76, 48.7%) or false positives by microscopy (31/76, 40.8%). The sensitivity of the Bioline Malaria Ag P.f/Pan combination RDT was high (> 91%) using either microscopy or qPCR as the gold standard. However, specificity was low (56.7%) when microscopy was used as the gold standard; it improved to 64.0% when qPCR was used as the gold standard. Conclusion The Bioline Malaria Ag P.f/Pan combination RDT was found to be highly sensitive in Uganda and reliable for ruling out malaria. False negative RDT results were primarily due to low density P. falciparum infections, non-falciparum infections, or incorrect microscopy results. In contrast, false positive RDT results were common, most likely due to persistent HRP2 antigenaemia in this high transmission setting though causes of false positive RDTs were not investigated. The low specificity of HRP2-based RDTs may result in overuse of anti-malarial drugs and missed diagnoses of non-malarial febrile illnesses.